2014
DOI: 10.1007/s12015-014-9539-7
|View full text |Cite
|
Sign up to set email alerts
|

Olfactory Ensheathing Cells Promote Differentiation of Neural Stem Cells and Robust Neurite Extension

Abstract: Aims The goal of this study was to gain insight into the signaling between olfactory ensheathing cells (OECs) and neural stem cells (NSCs). We sought to understand the impact of OECs on NSC differentiation and neurite extension and to begin to elucidate the factors involved in these interactions to provide new targets for therapeutic interventions. Materials and Methods We utilized lines of OECs that have been extremely well characterized in vitro and in vivo along with well studied NSCs in gels to determine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 79 publications
1
8
1
Order By: Relevance
“…Another example of contact mediated increase of axonal outgrowth induced by OECs includes DRG axons grown on myelin substrates [44]. In our study, the secretome of OECs did not reveal to be a growth promoting substrate for axonal outgrowth of DRG explants, even though there is a substantial body of literature supporting the relevance of OECs' secreted factors in axonal regeneration context [45][46][47]. The contact-mediated ability of OECs might be partially due to the action of metalloproteinases (MMPs) such as MMP-2, MMP-3, and MT1-MMP, which seem to play a role on cellular motility and on their neurotrophic properties [48].…”
Section: Discussioncontrasting
confidence: 60%
“…Another example of contact mediated increase of axonal outgrowth induced by OECs includes DRG axons grown on myelin substrates [44]. In our study, the secretome of OECs did not reveal to be a growth promoting substrate for axonal outgrowth of DRG explants, even though there is a substantial body of literature supporting the relevance of OECs' secreted factors in axonal regeneration context [45][46][47]. The contact-mediated ability of OECs might be partially due to the action of metalloproteinases (MMPs) such as MMP-2, MMP-3, and MT1-MMP, which seem to play a role on cellular motility and on their neurotrophic properties [48].…”
Section: Discussioncontrasting
confidence: 60%
“…It is known that in the CNS, the effects of glial cells on neuronal development differ according to their phenotype (Powell et al ., ; Rakic, ). Similarly, in the main olfactory system, in vitro and in vivo data from several studies have indicated that OEC can act differently in neuronal development according to their phenotypes (Kafitz & Greer, ; Wewetzer et al ., ; Lipson et al ., ; Zhang et al ., ; Su & He, ; Jiao et al ., ; Sethi et al ., ). Mature OECs expressing the neurotrophin receptor p75 NTR have been shown to increase neurite outgrowth significantly in brain slices (Jiao et al ., ).…”
Section: Discussionmentioning
confidence: 97%
“…They also aid in tissue repair by effecting structural remodeling and support, modulating the immune system, enhancing neurotrophic and antigenic stimuli and metabolizing toxic macromolecules. Finally, OECs may be transplanted together with growth factor (e.g., bFGF, or basic fibroblast growth factor) to sustain cell survival and proliferation [39][40][41] .…”
Section: Olfactory Ensheathing Cellsmentioning
confidence: 99%